Managing ischial apophysitis in an Indian national level weightlifter through a collaborative strength and rehabilitation program. - van Zyl, L. M. (Journal of Australian Strength and Conditioning, 2020)
Ischial apophysitis is a common injury among adolescent athletes. Research suggests that 22 to 55% of all apophyseal injuries involve the ischial tuberosity and in the general population injuries are more prevalent in males (67-90%). Risk factors that may predispose an athlete to ischial apophysitis include muscle fatigue, poor hamstring and quadriceps flexibility, previous history of injury, and a low hamstring to quadriceps ratio. Currently, little research exists to showcase the programming of a weightlifter rehabilitating and returning to sport after a diagnosis of ischial apophysitis. The aim of this case study is to describe a strength and rehabilitation program that was used to assist a national level weightlifter in returning to 70-90% of his one repetition maximum (1RM) (snatch, clean, back squat, front squat and deadlift) within two months from the initial diagnosis.